Computer assisted planning and custom-made surgical guide for malunited pronation deformity after first metatarsophalangeal joint arthrodesis in rheumatoid arthritis: A case report. (January 2014) - Hirao, Makoto; Ikemoto, Sumika; Tsuboi, Hideki; Akita, Shosuke; Ohshima, Shiro; Saeki, Yukihiko; Yoshikawa, Hideki; Sugamoto, Kazuomi; Murase, Tsuyoshi; Hashimoto, Jun
Abstract Arthrodesis of the first metatarsophalangeal (MTP-1) joint is a widely used procedure for the treatment of hallux valgus in patients with MTP-1 degeneration, severe or recurrent deformity, or inflammatory arthritis. In this case, ten years earlier, the patient's MTP-1 joint had been fused in a severe pronation deformity position. Subsequently, a laterally shifted tibial sesamoid and osseous rising of the phalanx base caused painful callosities. To correct the pronated deformity accurately, a custom-made surgical guide based on a three-dimensional computer tomography (3D-CT) simulation system was used. After correction of the deformity, the MTP-1 joint was again fused. Adequate correction was achieved, and the patient no longer complains of pain and can perform full weight-bearing on the forefoot. The difficulty and importance of placing the MTP-1 joint in an adequate rotational position in MTP-1 joint arthrodesis surgery were confirmed, as was the utility of 3D evaluation and a custom-made surgical guide for rotational adjustment between the metatarsal and the proximal phalanx. We believe that this system should be one of the indicators for adjusting the rotation, especially in revision MTP-1 joint fusion surgery.